Exploration of Antarctica - SEHRA, PARMJIT SINGH (SCHOOL SCIENCE, 2006)
ANTARCTICA is the name of a great continent covered with snow and ice that surrounds the South Pole. It is the 5th largest continent and covers about 14 million square kilometres, an area about the size of the United States and Mexico combined and has a coastline of 29,600 kms. Over countless years, snow and ice have built up on the land burying all but 4.5 per cent of it. The ice sheet counts for about 90 per cent of the world’s ice. If this were to melt, sea level would rise at least 75 metres.